Why policies on trade and markets matter - Díaz-Bonilla, Eugenio; Hepburn, Jonathan (2017)
Recent international commitments on food and nutrition security could have significant implications for trade and markets between now and 2030, if governments follow through on the Sustainable Development Goals (SDGs) they agreed at the UN General Assembly in September 2015. However, doing so will require them to work together towards shared objectives.